SARUNG INSTANT 2 IN 1 UNTUK MENINGKATKAN MOTIVASI ANAK DALAM BERIBADAH SHOLAT - Darmawan, Alfian; Gusti, Puspa Pertiwi Karestu; Prabowo, Nur Ichsan Wahyu; Fauzi, Naufal Annas (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Sarong is one of the main equipment to pray. But nowadays, sarong still has traditional form that makes children get difficulties in using sarong. Besides, the sarong motif is monotonous and canât catch childrenâs interest in praying. So, we create a unique, exclusive, and interesting sarong creation for children in form of sarong instant 2 in 1 to improve the childrenâs motivation in praying. Instant means easy to be used and 2 in 1 means the two-side of sarong can be used. The other advantages are combination of two colors can catch the childrenâs interest in praying, affordable prices, and product has not been available in the market. The production is conducted from mid-April until now with total product production is 48, 32 sold product, and 15 orders.